2004
DOI: 10.1182/blood-2003-02-0660
|View full text |Cite
|
Sign up to set email alerts
|

Protection from endotoxemia by adenoviral-mediated gene transfer of human bactericidal/permeability-increasing protein

Abstract: Sepsis represents a growing concern in high-risk patients and there has been a lack of effective preventives and therapies. Bacterial/permeability increasing protein (BPI) is a human neutrophil granule-associated defense molecule specific for Gram-negative bacteria and their products. To develop a BPI-transgene-based prophylactic or therapeutic modality, we have developed a recombinant, replication-deficient adenoviral vector expressing full-length human BPI protein (Adh- BPI IntroductionSepsis is a heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…BPI, another PLTP-related protein that neutralizes LPS, is a potent inhibitor of CD14-dependent cell activation by endotoxins, has direct Gram-negative bacterial killing properties, and enhances bacterial phagocytosis (36,51). Although BPI is normally an intracellular factor that is produced and stored in neutrophils and is not detected in plasma under normal physiological conditions (52), the overexpression of circulating forms of BPI or BPI fragments in mice was shown to provide protection from lethal endotoxemia (53,54). In humans, the injection of recombinant BPI was found to be effective in decreasing morbidity and functional outcomes in children with severe meningococcemia but with no significant decrease in mortality (55).…”
Section: Discussionmentioning
confidence: 99%
“…BPI, another PLTP-related protein that neutralizes LPS, is a potent inhibitor of CD14-dependent cell activation by endotoxins, has direct Gram-negative bacterial killing properties, and enhances bacterial phagocytosis (36,51). Although BPI is normally an intracellular factor that is produced and stored in neutrophils and is not detected in plasma under normal physiological conditions (52), the overexpression of circulating forms of BPI or BPI fragments in mice was shown to provide protection from lethal endotoxemia (53,54). In humans, the injection of recombinant BPI was found to be effective in decreasing morbidity and functional outcomes in children with severe meningococcemia but with no significant decrease in mortality (55).…”
Section: Discussionmentioning
confidence: 99%
“…In brief summary, in a variety of animal models, recombinant human BPI (rBPI) and its amino-terminal derivate (rBPI 21 ), were protective against lethal and sub-lethal challenges with Gram-negative bacteria and endotoxin [11,[58][59][60][61]. Subsequent studies in humans, including in meningococcal sepsis, also showed a significant protective effect of BPI [12][13][14][15][61][62][63][64], although not yet sufficient to lead to an approved clinical application.…”
Section: Bpi Actions During Host: Gnb Interactionsmentioning
confidence: 99%
“…8 Despite continuing progress in the development of antibiotics and other supportive care therapies, there is a lack of effective means of prevention of or therapy for sepsis. 8,9 Indeed, therapies directed at neutralizing LPS or proinflammatory cytokines can prevent the development of septic shock in animal models, but clinical trials of these therapies have in general failed to improve the outcome of patients with sepsis. 8,9 Therefore, there is great enthusiasm about the development of novel strategies for the treatment of sepsis.…”
Section: Introductionmentioning
confidence: 99%